Terahertz time-gated spectral imaging for content extraction through layered structures - Albert Redo-Sanchez (Nature Portfolio, 2016)
Terahertz radiation may be used to nondestructively detect and study defects and structures within materials. Here the authors use terahertz time-gated spectral imaging to extract occluded text from paper pages with subwavelength spacing.